Karakteristik nutrisi dalam yoghurt pada susu sapi, kambing dan oat - Zahra, Cheryl Dwi Nur; Leonita, Lastri; Alyasa, Rahadian Rasyid; Surtikanti, Hertien Koosbandiah; Priyandoko, Didik (Jurnal Inovasi Pangan dan Gizi, 2024)
Background: Yogurt is a dairy product produced by fermenting milk using starter cultures such as Lactobacillus bulgaricus and Streptococcus thermophilus bacteria. The use of these bacteria is due to their role in producing lactic acid. With the involvement of these bacteria, the liquid milk coagulates and develops a distinctive acidic taste. Methods: The research method employed in this article is qualitative research using a literature review approach. Finding: Based on the study results, it was found that cow's milk undergoes an increase in protein and carbohydrate levels after being transformed into yogurt. Goat's milk experiences an increase in carbohydrate and calcium levels post-yogurt production. Meanwhile, oat milk shows an increase in ash concentration and protein levels. Conclusion: The comparative results indicate that each yogurt from different sources offers distinct nutritional advantages. Therefore, it is important to consider the body's nutritional needs before consumption.